La enfermedad de Parkinson: un enfoque interdisciplinario - Aguilar, Luis (2016)
In this paper we summarize an interdisciplinary study on Parkinson´s disease. Members of the team were drawn from neuroscience, biology and complex sciences, biomedical engineering, and philosophy of mind. Due to its concentration and presence on reported nuclei, we suggest that neuropeptide Y may be considered a reliable indicator of this disease. If the neuro network participates on conscious experience, it would certainly play a role on consciousness. Moreover, on psychological and social levels, Parkinson´s disease is involved in the loss of identity which includes not only genetic and physiological factors, but environment interaction as well. Therefore, Parkinson´s disease should be considered a multi-level disease, ranging from the molecular to the social.